Crosstalk with Inflammatory Macrophages Shapes the Regulatory Properties of Multipotent Adult Progenitor Cells - Stylianos Ravanidis; Jeroen F. J. Bogie; Raf Donders; Robert Deans; Jerome J. A. Hendriks; Piet Stinissen; Jef Pinxteren; Robert W. Mays; Niels Hellings (Stem Cells International)
Macrophages and microglia are key effector cells in immune-mediated neuroinflammatory disorders. Driving myeloid cells towards an anti-inflammatory, tissue repair-promoting phenotype is considered a promising strategy to halt neuroinflammation and promote central nervous system (CNS) repair. In this study, we defined the impact of multipotent adult progenitor cells (MAPC), a stem cell population sharing common mesodermal origin with mesenchymal stem cells (MSCs), on the phenotype of macrophages and the reciprocal interactions between these two cell types. We show that MAPC suppress the secretion of tumor necrosis factor alpha (TNF-α) by inflammatory macrophages partially through a cyclooxygenase 2- (COX-2-) dependent mechanism. In turn, we demonstrate that inflammatory macrophages trigger the immunomodulatory properties of MAPC, including an increased expression of immunomodulatory mediators (e.g., inducible nitric oxide synthase (iNOS) and COX-2), chemokines, and chemokine receptors. Macrophage-primed MAPC secrete soluble factors that suppress TNF-α release by macrophages. Moreover, the MAPC secretome suppresses the antigen-specific proliferation of autoreactive T cells and the T cell stimulatory capacity of macrophages. Finally, MAPC increase their motility towards secreted factors of activated macrophages. Collectively, these in vitro findings reveal intimate reciprocal interactions between MAPC and inflammatory macrophages, which are of importance in the design of MAPC-based therapeutic strategies for neuroinflammatory disorders in which myeloid cells play a crucial role.